THE PSYCHOLOGICAL IMPACT OF PARENTAL LOSS ON ADOLESCENTS AT MADRASAH TSANAWIYAH IN PETATAL VILLAGE, BATU BARA REGENCY - Ulfi, Kholilah; Abdurrahman, Zulkarnain (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to determine the psychological impact of losing parents on adolescents at Madrasah Tsanawiyah Petatal Village, Datuk Tanah Datar Sub-district, Batu Bara Regency. The method used in the research is a qualitative approach with primary and secondary data as research data sources. The data analysis technique uses the Miles and Huberman model, which consists of three techniques including data reduction, data presentation, and conclusion drawing. The results stated that the loss of parents has a deep psychological impact on adolescents, which is reflected in their emotional, social, and academic changes. Adolescents who lose their parents often experience feelings of sadness, anxiety, confusion, and disorientation. These changes can interfere with their concentration in learning, as well as affect social relationships with friends and teachers in the Madrasah.